Professional nursing in the Philippines - Venzon, Lydia M.; Venzon, Ronald M. (Quezon City, Philippines : C & E Publishing Inc., 2016)
Professional Nursing in the Philippines is a handy and comprehensive guide for ail registered Filipino nurses who practice their profession here and abroad. The book aims to initiate neophyte nurses into the complex world of the nursing profession through discussions of salient features of important documents. For veteran nurses, several topics are included to keep them updated.
1. Nursing as a profession -- 2. License to practice nursing -- 3. The license board -- 4.Different fields of nursing -- 5. Nursing opportunities abroad -- 6. Choosing, retaining, resigning and dismissal from a position -- 7. Contracts -- 8. Nursing ethics -- 9. Moral and spiritual responsibilities of nurses -- 10. Code of ethics for filipino nurses -- 11. Laws governing the practice of nursing -- 12. Legal aspects and the nurse -- 13. Continuing education in nursing -- 14. Nursing association in the Philippines -- 15. International nursing and allied organizations.
Includes index.
Keywords: NURSING -- PRACTICE -- PHILIPPINES